Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1037/men0000115
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of symptoms of depression and anxiety among expectant and new fathers.

Abstract: Many men experience depression and anxiety during the transition to parenthood, but characteristics associated with fathers’ distress are less well understood than those for mothers. Among perinatal women, both general cognitive biases and attitudes toward parenthood are associated with symptoms of depression and anxiety. The goal of this study was to assess whether these characteristics are associated with psychological distress among fathers. An Internet-based sample of expectant (n = 145) and new (n = 137) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Transition to fatherhood has been under-investigated compared to the transition to motherhood (Recto and Champion, 2020 ). However, some research has identified dysfunctional cognition and external locus of control as risk factors for the development of depressive symptoms during this transition to fatherhood (Keeton et al, 2008 ; Sockol and Allred, 2018 ). Holding dysfunctional cognitions and beliefs may be especially relevant during the transition to parenthood, due to the shift in demands from one's own needs to looking after a dependent child.…”
Section: Discussionmentioning
confidence: 99%
“…Transition to fatherhood has been under-investigated compared to the transition to motherhood (Recto and Champion, 2020 ). However, some research has identified dysfunctional cognition and external locus of control as risk factors for the development of depressive symptoms during this transition to fatherhood (Keeton et al, 2008 ; Sockol and Allred, 2018 ). Holding dysfunctional cognitions and beliefs may be especially relevant during the transition to parenthood, due to the shift in demands from one's own needs to looking after a dependent child.…”
Section: Discussionmentioning
confidence: 99%
“…As such the findings of the current review are more applicable to women at high-risk of mental health issues, limiting generalizability to women at low risk. It is important to note however that general populations may include individuals with stress and anxiety symptoms that could become exacerbated as pregnancy progresses and/or in early parenthood due to the stressful transitional nature of this period [23,24]. Robust longitudinal examinations of interventions that provide skills to manage stress and anxiety across the first 1000 days are needed to better determine effects of preventive, in addition to reduction-focused, interventions.…”
Section: Study Populations Included In Reviewed Studiesmentioning
confidence: 99%
“…Inclusion of partners in future stress and/or anxiety reduction interventions in the first 1000 days should also be considered. Though fathers tend to report lower stress and anxiety than mothers [20], paternal stress is associated with maternal stress [27], perceived social support [24], and child development [71]. Only two reviewed interventions included fathers, and these were delivered postpartum to fathers of preterm infants with inconsistent effects [49,50].…”
Section: Study Populations Included In Reviewed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in this issue focus on how the quality of these relationships is associated with son’s body mass index (Coleman, O’Neil, Caldwell, & Ferris, 2019) and how fathers’ eating habits may be influenced by their son’s experiences of discrimination—perhaps as a form of coping (Coleman, O’Neil, & Ferris, 2019). These articles follow the growing number of PMM articles that have been focusing on the importance of fathers’ involvement in childcare (Kuo, Volling, & Gonzalez, 2018; Lee & Lee, 2018; Trahan, 2018), the psychological challenges of fatherhood (Sockol & Allred, 2018; Zerach & Magal, 2017), the need for fathers to focus on self-care (Nash, 2018; Rominov, Giallo, Pilkington, & Whelan, 2018), and the experience of being a father among non-Western men (Barrocas, Vierira-Santos, Paixão, Roberto, & Pereira, 2017; Kasymova & Billings, 2018). Indeed, fatherhood was identified as a growing area of interest in PMM ’s publication profile, and as an area of inquiry potentially fruitful for grant-funded research (Parent et al, 2018).…”
Section: This Special Issue Of Pmmmentioning
confidence: 99%